An Econometric Research on the Economic Effects of Tax Amnesties - Kanca, Osman Cenk; Bayrak, Metin (International Journal of Economics and Financial Issues, 2024)
Nowadays, especially developing countries need different resources to meet their expenditures. In this context, the issue of tax amnesties maintains its place on the agenda both in the economic and political arena. The economic effects of tax amnesties are still discussed in the literature. In this study, the relationship between tax amnesties and some macroeconomic variables (tax revenues, inflation, growth) has been econometrically tested for Turkey for the period of 1980-2021. In the study, in which ARDL model was used, cointegration relationship was determined between tax amnesties, tax revenues, inflation and growth. In addition, it has been determined that tax amnesties have positive effects on growth and inflation through tax revenues in both the short and long run.